Identity sociological perspectives - Lawler, Steph 1958- (Cambridge, [England] Polity Press, 2014)
Lawler examines debates surrounding identity, and shows how identity is part of the fabric of society, and integral to social relations. The book includes all the core topics covered by courses in this field and uses rich and varied contemporary empirical examples to illustrate the discussion.
1. Introduction: identity as a question -- 2. Stories, memories, identities -- 3. Who do you think you are? Kinship, inheritance and identity -- 4. Becoming ourselves: governing and/through identities -- 5. I desire therefore I am: unconscious selves -- 6. Masquerading as ourselves: self-impersonation and social life -- 7. The hidden privileges of identity: on being middle class -- 8. Identity politics, identity and politics.
sIncludes bibliographical references (pages 190-202) and index.
Keywords: Group identity; Identity (Psychology) -- Social aspects; Socialization